Identification and Contribution of Inflammation-Induced Novel MicroRNA in the Pathogenesis of Systemic Lupus Erythematosus - Singh, Ram P.; Hahn, Bevra H.; Bischoff, David S. (Frontiers in Immunology, 2022)
Recently microRNAs (miRNAs) have been recognized as powerful regulators of many genes and pathways involved in the pathogenesis of inflammatory diseases including Systemic Lupus Erythematosus (SLE). SLE is an autoimmune disease characterized by production of various autoantibodies, inflammatory immune cells, and dysregulation of epigenetic changes. Several candidate miRNAs regulating inflammation and autoimmunity in SLE are described. In this study, we found significant increases in the expression of miR21, miR25, and miR186 in peripheral blood mononuclear cells (PBMCs) of SLE patients compared to healthy controls. However, miR146a was significantly decreased in SLE patients compared to healthy controls and was negatively correlated with plasma estradiol levels and with SLE disease activity scores (SLEDAI). We also found that protein levels of IL-12 and IL-21 were significantly increased in SLE patients as compared to healthy controls. Further, our data shows that protein levels of IL-12 were positively correlated with miR21 expression and protein levels of IL-21 positively correlated with miR25 and miR186 expression in SLE patients. In addition, we found that levels of miR21, miR25, and miR186 positively correlated with SLEDAI and miR146a was negatively correlated in SLE patients. Thus, our data shows a dynamic interplay between disease pathogenesis and miRNA expression. This study has translational potential and may identify novel therapeutic targets in patients with SLE.